Case report: Novel insights into hemorrhagic destruction of the brain, subependymal calcification, and cataracts disease - Abdallah Moady, Tameemi; Odeh, Marwan; Fedida, Ayalla; Segal, Zvi; Gruber, Maayan; Goldfeld, Moshe; Kalfon, Limor; Falik-Zaccai, Tzipora C. (Frontiers in Pediatrics, 2023)
Introduction Pathogenic variants of the junctional adhesion molecule 3 (JAM3/JAM-C; OMIM#606871) is the cause of the rare recessive disorder called hemorrhagic destruction of the brain, subependymal calcification, and cataracts (HDBSCC, OMIM#613730) disease. A similar phenotype is universal, including congenital cataracts and brain hemorrhages with high mortality rate in the first few weeks of life and with a poor neurologic outcome in survivors. We aim to describe and enlighten novel phenotype and genotype of a new patient and review the literature regarding all reported patients worldwide. Case report We report the case of a prenatal and postnatal phenotype of a new patient with a novel pathogenic loss-of-function variant in JAM3, who presented prenatally with cataracts and brain anomalies and postnatally with brain hemorrhages, failure to thrive (FTT), progressive microcephaly, recurrent posterior capsule opacities, and auditory neuropathy. Discussion This study enlightens novel possible functions of JAM3 in the normal development of the brain, the ocular lenses, the auditory system, and possibly the gastrointestinal tract. This study is the first to report of cataracts evident in as early as 23 weeks of gestation and a rare phenomenon of recurrent posterior capsule opacities despite performing recurrent posterior capsulectomy and anterior vitrectomy. We suggest that auditory neuropathy, which is reported here for the first time, is part of the phenotype of HDBSCC, probably due to an endothelial microvasculature disruption of the peripheral eighth nerve or possibly due to impaired nerve conduction from the synapse to the brainstem. Conclusions Prenatal cataracts, brain anomalies, FTT, and auditory neuropathy are part of the phenotype of the HDBSCC disease. We suggest including JAM3 in the gene list known to cause congenital cataracts, brain hemorrhages, and hearing loss. Further studies should address the auditory neuropathy and FTT phenomena in knockout mice models. We further suggest performing comprehensive ophthalmic, audiologic, and gastroenterologic evaluations for living patients worldwide to further confirm these novel phenomena in this rare entity.